2014 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2014
DOI: 10.1109/icassp.2014.6855011
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Eigenvalue detection for spectrum sensing under correlated noise

Abstract: Herein, we consider the problem of detecting primary users' signals in the presence of noise correlation, which may arise due to imperfections in filtering and oversampling operations in a Cognitive Radio (CR) receiver. In this context, we study a Maximum Eigenvalue (ME) detection technique using recent results from Random Matrix Theory (RMT) for characterizing the distribution of the maximum eigenvalue of a class of sample covariance matrices. Subsequently, we derive a theoretical expression for a sensing thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…MED [12], minimum eigenvalue (ME) [13], two stage spectrum sensing detection (ED and CMME) [14], energy and eigenvalue based detections combined as fully blind and self adaptive [15]. The implementation of this dual stage detection scheme has been carried out using GNU radio and USRP.…”
Section: Network Protocols and Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…MED [12], minimum eigenvalue (ME) [13], two stage spectrum sensing detection (ED and CMME) [14], energy and eigenvalue based detections combined as fully blind and self adaptive [15]. The implementation of this dual stage detection scheme has been carried out using GNU radio and USRP.…”
Section: Network Protocols and Algorithmsmentioning
confidence: 99%
“…It is observed that the threshold calculated for uncorrelated scenario when applied to correlated scenarios, the fa P value gets deviated from the targeted fa P value. To address this problem, threshold function is derived for correlated noise [12].…”
Section: Maximum Eigenvalue Based Detection For Correlated Noisementioning
confidence: 99%
“…By using different eigenvalue properties of R Y (N ) such as Maximum Eigenvalue (ME) [17], Signal Condition Number (SCN) [4,15], Scaled Largest Eigenvalue (SLE) [14], etc., the presence or absence of the PU signal can be decided. 2.…”
Section: System and Signal Modelmentioning
confidence: 99%
“…Noise/Channel Correlation Although recent works [36], [140] have proposed new sensing bounds for SCN and ME based sensing under noise correlated scenarios, analyzing the effect of noise correlation on the performance of other detectors as well as investigation of new sensing bounds which provide improved detection performance under correlated scenarios is still an open research challenge. Future research should focus on investigating suitable approaches while considering these imperfections into account.…”
Section: Quantization Errorsmentioning
confidence: 99%
“…To address the aforementioned issue, new sensing thresholds for SCN and ME based techniques have been proposed in [139], [140] using recent results from RMT in order to achieve the improved sensing in correlated noise scenarios. The analysis has been carried out by considering a one-sided exponential correlation model to include noise correlation across the receive dimensions and the similar analysis is applicable for temporally correlated case assuming the exponential correlation model still holds.…”
Section: Noise/channel Correlationmentioning
confidence: 99%